Mind the body: Mindfulness meditation as a spiritual practice between neuroscience, therapy and self-awareness - Nehring, Andreas (The Palgrave Handbook of Embodiment and Learning, 2022)
Over the last few decades, the Buddhist concept of mindfulness has become popular in many Western societies. Viewed by its proponents as a non-confessional practice of self-experience, mindfulness meditation belongs to what social scientists term 'spirituality' rather than a more traditional understanding of 'religion'. The acceptance and effectiveness of mindfulness are perceived in therapeutic, religious and pedagogical fields. The acceptance of mindfulness can be explained by focussing on the cultural preconditions of its reception in the Global West. A cultural studies approach analyses the concept and practice of mindfulness under contemporary, cultural conditions. Mindfulness as a practice cannot be separated from discourses of legitimation and interpretation.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Body-knowledge; Buddhism; Mindfulness; Spirituality